Dampak Kompetensi Perangkat Desa pada Efektivitas Pengelolaan Dana Desa: Moderasi Moralitas - Antari, Ni Wayan Indah; Sinarwati, Ni Kadek; Atmadja, Anantawikrama Tungga (Jurnal Samudra Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of village apparatus competence on the effectiveness of village fund management and to examine the role of morality as a moderating variable. This study used a quantitative approach with a survey method of 108 village apparatus respondents in Denpasar City. The research instrument used three validated and tested questionnaires for reliability. Data analysis was conducted using path analysis and t-tests using SEM-PLS. The results showed that village apparatus competence had a positive and significant effect on the effectiveness of village fund management. However, morality was not proven to moderate this relationship. This finding indicates that management effectiveness is not only determined by competence and moral values, but is also influenced by other systemic factors. It is recommended that village apparatus development not only focus on technical aspects, but also strengthen ethics and organizational work systems.